2013
DOI: 10.4070/kcj.2013.43.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Cardiac MR Imaging for Myocardial Characterization and Quantification: T1 Mapping

Abstract: Magnetic resonance as an imaging modality provides an excellent soft tissue differentiation, which is an ideal choice for cardiac imaging. Cardiac magnetic resonance (CMR) allows myocardial tissue characterization, as well as comprehensive evaluation of the structures. Although late gadolinium enhancement after injection of the gadolinium extracellular contrast agent has further extended our ability to characterize the myocardial tissue, it also has limitations in the quantification of enhanced myocardial tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“… 17 In recent years, a major interest in T1 mapping has focused on the significant correlation between the degree of fibrosis and increased T1 relaxation time. 17 , 19 21 Reported correlations between histological collagen volume fraction determined from biopsy samples obtained during surgery for aortic valve replacement and T1 were good, with r = 0.65 26 and r = 0.78. 27 …”
Section: Fibrosismentioning
confidence: 97%
See 1 more Smart Citation
“… 17 In recent years, a major interest in T1 mapping has focused on the significant correlation between the degree of fibrosis and increased T1 relaxation time. 17 , 19 21 Reported correlations between histological collagen volume fraction determined from biopsy samples obtained during surgery for aortic valve replacement and T1 were good, with r = 0.65 26 and r = 0.78. 27 …”
Section: Fibrosismentioning
confidence: 97%
“…Fibrosis, which constitutes a common and final pathway in several cardiac diseases, may be discrete, focal (scar), or diffuse (uniform interstitial process). [19][20][21] Expansion of the collagen matrix increases the volume of distribution (approximately from 20% to 30%), leading to combined pre-contrast T1 augmentation and greater gadolinium uptake (shorter post-contrast T1). Thus, focal lesions are assessable by both T1 mapping and LGE techniques.…”
Section: Fibrosismentioning
confidence: 99%
“…Not only fibrosis but also inflammation and edema can be picked up by T 1 -weighted mapping, and an increase in signal is thus related to an increase in the extracellular volume and not an increase in fibrosis per se. 26 In contrast to dye stainings, CNA35 specifically binds to fibrillar collagen, whereas stainings such as PSR and Masson's trichrome are based on base-acid interactions and therefore may not be entirely collagen specific. In addition, in this study, it was shown that CNA35 can detect cardiac collagen after in vivo administration, which to our knowledge is not possible with other dyes.…”
Section: Discussionmentioning
confidence: 99%
“…T2-weighted images scanned by the turbo spin echo sequence show fewer susceptibility artifacts [16,23]. Myocardial T1 CMR maps also have weak susceptibility for artifacts because the T1 CMR map is based on the SSFP sequence [5]. CMR protocol modifications have been suggested to minimize CEID-related artifact in CMR images (Table 4).…”
Section: Cviamentioning
confidence: 99%
“…Cardiac magnetic resonance (CMR) examination has rapidly increased in use and application as a novel hardware, software, and processing technique [2]. Thus, CMR imaging has become a valuable tool for non-invasive heart disease detection and characterization [2][3][4][5]. Cardiac implantable electronic device (CIED) generally refers to implanted cardiac pacing devices, such as the cardiac pacemaker (PM), implantable cardioverter defibrillator (ICD), and cardiac resynchronization therapy (CRT) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%